2023
DOI: 10.3390/agronomy13102592
|View full text |Cite
|
Sign up to set email alerts
|

The Microbiomes of Various Types of Abandoned Fallow Soils of South Taiga (Novgorod Region, Russian North-West)

Evgeny V. Abakumov,
Grigory V. Gladkov,
Anastasiia K. Kimeklis
et al.

Abstract: More than 30 years have passed after the collapse of the Soviet Union, and huge areas of soil were left in a fallow state. The study of the microbiological status of fallow soils is an extremely urgent task because fallow soils represent the “hidden” food basket of Eurasia. In this context, we studied the influence of land use type (pasture, vegetable garden, hayfield, or secondary afforestation) on key agrochemical parameters and parameters of soil microbial biodiversity. All anthropogenically transformed soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…(1) The management and utilization of traditional grasslands [16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Overview Of the Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…(1) The management and utilization of traditional grasslands [16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Overview Of the Special Issuementioning
confidence: 99%
“…As for the health evaluation and management of grasslands, Shi et al [26] developed a sound warning system to diagnose the potential degradation risk of alpine grasslands, and this study is crucial for understanding the health level of alpine grassland and its further change trends and providing an important scientific basis for rational grazing. Abakumov et al [27] studied the influence of land use type (pasture, vegetable garden, hayfield, or secondary afforestation) on key agrochemical parameters and the parameters of soil microbial biodiversity and found that the key factor regulating soil microbiome composition shifts was the duration and degree of the irreversibility of an agrogenic impact. Xiong et al [28] analyzed 143 pertinent works on grassland ecological assets and ecological products and proposed insights into the enhancement of karst grassland ecosystem service functions based on three perspectives: a fragile environment, trade-off synergy, and service management.…”
Section: The Management and Utilization Of Traditional Grasslandsmentioning
confidence: 99%